Xenodiagnosis to address key questions in visceral leishmaniasis control and elimination. - Om Prakash Singh; Epco Hasker; Marleen Boelaert; David Sacks; Shyam Sundar (Public Library of Science (PLoS), 2020)
Visceral leishmaniasis (VL) remains an important public health issue worldwide causing substantial morbidity and mortality. The Indian subcontinent accounted for up to 90% of the global VL burden in the past but made significant progress during recent years and is now moving towards elimination. However, to achieve and sustain elimination of VL, knowledge gaps on infection reservoirs and transmission need to be addressed urgently. Xenodiagnosis is the most direct way for testing the infectiousness of hosts to the vectors and can be used to investigate the dynamics and epidemiology of Leishmania donovani transmission. There are, however, several logistic and ethical issues with xenodiagnosis that need to be addressed before its application on human subjects. In the current Review, we discuss the critical knowledge gaps in VL transmission and the role of xenodiagnosis in disease transmission dynamics along with its technical challenges. Establishment of state of the art xenodiagnosis facilities is essential for the generation of much needed evidence in the VL elimination initiative.